Outcome of vein of Galen malformation presenting in the neonatal period. Issue 11 (23rd May 2019) - Malarbi, Stephanie; Gunn-Charlton, Julia K; Burnett, Alice C; Prentice, Trisha M; Williams, Amy; Mitchell, Peter; Wray, Alison; Hunt, Rod W
Abstract : Objective: Vein of Galenaneurysmal malformation (VGAM) is a rare but important congenital malformation presenting to neonatal intensive care units (NICUs), and with a change from surgical to endovascular management, survival for this condition has improved. However, there is little reported about the medical management decisions of infants with this condition and the associated long-term neurodevelopmental outcomes. We aim to report a single centre experience of both acute treatment and long-term outcomes of VGAM for those infants admitted to our NICU soon after birth. Design: Retrospective cohort study over a 15-year period from 2001 to 2015 inclusive. Setting: A quaternary NICU at The Royal Children's Hospital, Melbourne, Australia. Participants: 24 newborn infants referred for management of VGAM. There were no eligibility criteria set for this study; all presenting infants were included. Interventions: None. Main outcomes measures: Clinical neuroimaging data were gathered. Surviving children were formally assessed with a battery of tests administered by a neuropsychologist and occupational therapist/physiotherapist at various ages across early to middle childhood. Results: Fifteen neonates with VGAM did not survive beyond their NICU admission. 10 of these were not offered endovascular intervention. Of the nine surviving infants, only one had a normal neurodevelopmental outcome. Conclusions: The mortality of VGAM presenting in the neonatal period was high, and rates of normal neurodevelopmental outcome for survivors were low. These findings contribute to our understanding of which neonates should be treated and highlights the importance of providing clinical neurodevelopmental follow-up to survivors beyond their infant years.